2021
DOI: 10.1002/alz.12310
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's disease alters oligodendrocytic glycolytic and ketolytic gene expression

Abstract: Introduction Sporadic Alzheimer's disease (AD) is strongly correlated with impaired brain glucose metabolism, which may affect AD onset and progression. Ketolysis has been suggested as an alternative pathway to fuel the brain. Methods RNA‐seq profiles of post mortem AD brains were used to determine whether dysfunctional AD brain metabolism can be determined by impairments in glycolytic and ketolytic gene expression. Data were obtained from the Knight Alzheimer's Disease Research Center (62 cases; 13 controls),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 69 publications
0
22
0
Order By: Relevance
“…Studies using PET ketone tracer 11C-acetoacetate (AcAc) reported that brain metabolism of ketones is unchanged in MCI and early AD 73,74 supporting the previous assumption that oxidative phosphorylation may still be normal in early AD. Finally, a recent study utilizing RNA-seq on post mortem AD brains showed impaired glycolytic pathways in neurons and astrocytes while the ketolytic pathways remained normal 75 . Altogether, this suggests that early brain hypometabolism in AD may be specific to glycolytic breakdown 76 and not in dysfunctional mitochondrial oxidative phosphorylation.…”
Section: The Resulting Accumulation Of Aβ1-42 Is Key To the Pathogenesis Of Ad And Is Known To Inducementioning
confidence: 96%
“…Studies using PET ketone tracer 11C-acetoacetate (AcAc) reported that brain metabolism of ketones is unchanged in MCI and early AD 73,74 supporting the previous assumption that oxidative phosphorylation may still be normal in early AD. Finally, a recent study utilizing RNA-seq on post mortem AD brains showed impaired glycolytic pathways in neurons and astrocytes while the ketolytic pathways remained normal 75 . Altogether, this suggests that early brain hypometabolism in AD may be specific to glycolytic breakdown 76 and not in dysfunctional mitochondrial oxidative phosphorylation.…”
Section: The Resulting Accumulation Of Aβ1-42 Is Key To the Pathogenesis Of Ad And Is Known To Inducementioning
confidence: 96%
“…Using a 4-year longitudinal study in healthy older adults, we later showed that while declining regional brain glucose utilization (-6 to -12%) was paralleled by deteriorating cognitive performance, AcAc utilization remained unchanged over the same period (100) . A study in postmortem AD brains recently supported these in vivo observations by showing that while glycolytic gene expression was impaired in all cell types, ketolytic gene expression was normal in neurons, astrocytes and microglia but sub-normal in oligodendrocytes (101) . Overall, the impairment in brain energy metabolism in AD clearly seems to be specific to glucose, which opens the possibility of providing ketones as an alternative substrate to the brain to reduce or bypass the energetic deficit in AD caused by BGH.…”
Section: Brain Ketone Metabolism In Health and Alzheimer's Diseasementioning
confidence: 83%
“…RNA-Seq and proteomics based on mass spectrometry are widely used technologies that provide molecular-level insights into neurodegenerative diseases such as AD [ 53 , 54 , 55 , 56 ]. However, few studies have used an orthology approach to understand the diversity of AS manifestations in the CC and OB in humans and mice.…”
Section: Discussionmentioning
confidence: 99%
“…PKM2 is generally more abundant in embryonic stem cells [ 88 ] and organs with low energy demands, while PKM1 is more abundant in skeletal muscle, heart, and brain tissues [ 89 ]. A recent study demonstrated that AD alters glycolytic gene expression, including PKM , on oligodendrocytes [ 53 ]. Martire and colleagues found PKM1 overexpression in AD transgenic TgCRND8 mice at three months of age [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation